Neural procedures for the hybrid FEM/NN analysis of elastoplatic plates - Kaczmarczyk, Łukasz; Waszczyszyn, Zenon (Computer Assisted Methods in Engineering and Science, 2005)
A neural procedure was formulated in [4] as BPNN (Back-Propagation Neural Networks) for the simulation of generalized RMA (Return Mapping Algorithm). This procedure was evaluated to be too large to make a corresponding hybrid FEM/BPNN numerically efficient. That is why two new procedures NPI and NP2 were formulated. A description of their efficiency is presented in the paper, related to the computation number of computer operations and CPU time, carried out by FEM program FEAP and two hybrid programs FEAP/NP1 and FEAP/NP2.